ANALISIS KINERJA KEUANGAN RSUD SITI FATIMAH AZ- ZAHRA PROVINSI SUMATERA SELATAN MENGGUNAKAN PENDEKATAN VALUE FOR MONEY - Rahmattullah, M. Agung; Sari, Kartika Rachma; Armaini, Rosy (LPPM Universitas Bina Bangsa, 2024)
This research has a purposeto to analyze the financial performance of Siti Fatimah Az-Zahra Regional Hospital, South Sumatra Province during 2019 to 2023 using the Value For Money concept, which is measured through economic ratios, efficiency and effectiveness. This research is classified as descriptive research with a quantitative approach. Primary data was collected through interviews, while secondary data was obtained from the Budget Realization Report (LRA) and Operational Report (LO) of Siti Fatimah Az-Zahra Regional Hospital, South Sumatra Province. The results of this research show that during the period 2019 to 2023 the concept of value for money Using economic ratios, it can be concluded that the hospital's financial performance during the period analyzed tends to be uneconomical. The average percentage of expenditure realization reached 108,39%, indicating that expenditure exceeded the predetermined budget. Furthermore, using the efficiency ratio during the period 2019 to 2023, where Siti Fatimah Regional Hospital has shown a good level of efficiency in the use of funds, with an average value of 123.35%, and based on the effectiveness ratio for the period 2019 to 2023, it shows that during the observation period, the average effectiveness ratio of 125.67% was classified as effective